IMPLEMENTASI PEMBELAJARAN DARING PAI BERBASIS SOFT SKILL DI SMA NEGERI 5 MALANG - Yulia Dewi Budiani; Maskuri Bakri; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Implementation of learning is the application of curriculum plans (programs) in the form of learning, involving student interaction with teachers in the context of schooling. Soft skill-based online learning is learning that takes place in a network where the teacher and those being taught do not meet face-to-face. Soft skill-based online learning is learning that in its application emphasizes the formation of students' personality characters, namely intrapersonal and interpersonal characters. From the background of the research above, the researchers formulated problems, namely the implementation of soft skill-based PAI online learning, the effectiveness of soft skills-based PAI online learning, controlling soft skills-based PAI online learning, and evaluating soft skills-based PAI online learning. The purpose of this study is to describe the implementation of soft skill-based PAI online learning, planning for the implementation of soft skill-based Islamic Religious Education online learning, the implementation of soft skills-based Islamic Religious Education online learning, and the effectiveness and results of the implementation of Islamic Religious Education online learning based on soft skills. .